Design and Implementation of a Smart Healthcare Communication Bot - Sri. G. Kalyan Chakravarthi; D. Eekshitha; D. Srija; T. Jagadesh; Y. Sai Kamalesh (International Journal of Robotics and Automation in Mechanics, 2024)
Healthcare has proved to be one of the core factors that lead us to a magnificent life. Moreover, going to a professional for every small health issue is complicated and difficult task. To aid users with health issues, this paper describes the creation and deployment of a multifunctional healthcare assistance application. The application encompasses: The first task of the application involves a chatbot interface that gives in- depth drug information after the drug name is provided by user as input. The second task focuses on disease prediction, where users input their symptoms, and the application analyses the symptoms and predicts potential diseases or health conditions. Lastly, the application integrates with Google Maps to provide real-time navigation to nearest healthcare facilities based on their location.
Keywords: Functionalities interface; disease prediction; integrates; potential; real -time navigation